The Effect of Problem Based Learning on Fifth-Grade Students’ Speaking Ability in Oral Presentations of Short Stories - Rismayanti, Tuti; Rahmat Kartolo; Sutikno (PT Inovasi Pratama Internasional, 2026)
This study aims to determine the effect of the Problem Based Learning (PBL) model on students' speaking ability in oral presentations about short stories in grade V of State Elementary School 108 Aekmata, Mandailing Natal Regency, Academic Year 2025–2026. This study used a quantitative approach with a pre-experimental design of one-group pretest-posttest type. The subjects of the study were all 23 fifth grade students, who were selected using a saturated sampling technique. Data were collected through speaking ability tests before and after treatment, and analyzed descriptively and inferentially using the t-test. The results showed that before the implementation of the PBL model, the average pretest score of students' speaking ability was 65.43. At this stage, the majority of students were in the